Adopting Entrepreneurship Education—Teachers′ Professional Development. (3rd April 2023) - Oksanen, Lea; Oikkonen, Elena; Pihkala, Timo
This study explores teachers' professional development in entrepreneurship education (EE). It examines empirically the change in teachers' EE practices among Finnish teachers in 2011–2017. Overall, the quantitative analysis reveals that entrepreneurship education practices are increasing, albeit unevenly. Three groups of teachers, EE experimenters, EE critics, and EE selectors show different profiles in their use of EE practices. Furthermore, these groups seem to represent different stages of EE professionalization. The analysis shows that teachers' EE practices increase on the introductory stage but decrease deeply after. Moreover, the study suggests that teachers' implementation of EE evolves along with their teaching experience. It reveals that teachers in different stages of professional development need different types of support and that the adoption of EE practices depends on the institutional and social support offered to teachers. The results of the investigation contribute to the literature of EE by introducing a new typology of teachers, also presenting empirical evidence of the teachers' ability to absorb EE as a new approach. Furthermore, the study shows that for the adoption of EE it is not enough to emphasize the introductory stage but instead also the later stages of teacher's professionalization need to be considered.